Perkembangan Madrasah Hadis di Basrah, Kufah, dan Syam: Kajian Historis dan Metodologis - Hidayatulah Abdul Rachman; Engkos Kosasih; Isra Mardi (Cakrawala: Journal of Religious Studies and Global Society, 2025)
This study examines the historical development of hadith, the characteristics of hadith schools, and the driving and inhibiting factors of its dissemination in three major centers of Islamic civilization: Basrah, Kufah, and Syam. Employing a historical-critical approach, data were collected through literature studies of primary and secondary sources and analyzed using a descriptive-analytical method. The findings reveal that Basrah is known for its rationalist methodology, Kufah excels in the tradition of transmission criticism, while Syam demonstrates a synthesis of traditionalist approaches and extensive hadith dissemination practices. However, political conflicts, sectarian differences, and limited access to scholars are the primary obstacles to hadith development in these regions. These findings underscore the importance of an integrative approach in hadith studies, harmonizing traditional and modern methods to better understand the legacy of Islamic scholarship. This research also encourages cross-regional and periodical studies to enrich comprehensive insights into hadith history, offering a fresh perspective for contemporary Islamic studies.